Clonal relatedness in the acquisition of intestinal carriage and transmission of multidrug resistant (MDR) Klebsiella pneumoniae and Escherichia coli and its risk factors among preterm infants admitted to the neonatal intensive care unit (NICU) - Yee Qing Lee; Azanna Ahmad Kamar; Rukumani Devi Velayuthan; Chun Wie Chong; Cindy Shuan Ju Teh (Pediatrics and Neonatology)
Background: Gastrointestinal carriage of multidrug resistant (MDR) Gram-negative bacilli, especially Klebsiella pneumoniae and Escherichia coli, was highly associated with severe nosocomial infections. The main objectives of this study were to determine the clonal relatedness of intestinal carriage and transmission risk factors of MDR E. coli and K. pneumoniae amongst preterm infants admitted to the neonatal intensive care unit (NICU). Methods: A prospective cohort study of preterm infants with gestational age < 37 weeks was conducted in the NICU of the University of Malaya Medical Centre (UMMC). Infants' stool specimens were collected on day 1 (meconium), week 1, week 2, week 8 and week 10 during their admission (from 1st June to 31st August 2017) until discharge. The presence and antibiotic resistance pattern of MDR E. coli and K. pneumoniae were determined. Strain clonality and relatedness were explored via pulsed-field gel electrophoresis (PFGE) fingerprints. The risk factors for MDR strains acquisition were evaluated using the Cox proportional-hazards model and Firth logistic regression. Results: A total of 139 stool specimens were obtained from 50 subjects. Twenty-six (52%) infants were colonized with MDR K. pneumoniae and/or E. coli. High clonal dissemination between two clusters of ESBL-producing K. pneumoniae strains was seen from PFGE profile. We detected a persistent, dominant, aminoglycosides-resistant strains cluster (cluster B), which harbored blaTEM, blaSHV, blaOXA-1, blaCTX-M-1, ompK35 and ompK36 genes. Infants born to women who were anemic in pregnancy [OR = 0.01 (CI = 0.00–0.39), P-value = 0.042] and infants exposed to penicillin/β-lactams group antibiotics during the first week of life [OR = 0.02 (CI = 0.02–0.32), P-value = 0.013] were found to have a lower risk of MDR K. pneumoniae and E. coli colonization. Conclusions: The prevalence of dominant aminoglycosides-resistant strains cluster in the NICU is alarming. Awareness of and vigilance for the dominant cluster found will enable the reduction of cross-transmission amongst high-risk infants.